PENGUATAN LITERASI ANAK DENGAN BERMAIN PROYEK DI PENDIDIKAN ANAK USIA DINI - Mochamad Basri Fahrudin; Rita Aryani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
Child-centered education is very necessary for Early Childhood Education (PAUD). The ability to read and write must be possessed by children as early as possible. The method used in this research is descriptive qualitative. The results of this research are that children enjoy playing with their projects with the teacher stimulating them with open questions, so that every day the children want to write words according to the projects they make. Each child makes a different project so that the words written by the children are also different, in other words, children's literacy increases and increases by knowing new words from the projects they make. So project-based learning can increase children's literacy by adding new words and writing according to the child's abilities and thinking power to make the project fun for the child.